Rigor, relationships, and religion: exploring youth’s experience in after-school programs - English, Alan (Kansas State University, 2018)
This study addressed an existing gap in research on after-school programs, a lack of qualitative research. It consisted of a case study, conducted through a phenomenological theoretical framework, aimed to explore the experiences of four youth enrolled in a privately-funded, faith-based after-school program in an urban Midwest community. Unlike most after-school programs, the program studied provides services to youth that run continuously from sixth grade through high school graduation. Research was conducted primarily through observation at both the youth’s public school affiliated with the program and at program events outside of school, as well as both group and individual interviews. The Hirsch, Deutsch, & DuBois (2011) conceptual framework of the role of comprehensive after-school programs on youth, the Rhodes (2005) Model of Youth Mentoring, and the philosophy of positive youth development were key to this study.
Keywords: After-school programs; Positive youth development; Phenomenology; Mentor-youth relationships; Youth motivation